Sclerostin Neutralizing Antibody Treatment Enhances Bone Formation but Does Not Rescue Mechanically Induced Delayed Healing. (23rd May 2018) - Kruck, Bettina; Zimmermann, Elizabeth A; Damerow, Sophie; Figge, Christine; Julien, Catherine; Wulsten, Dag; Thiele, Tobias; Martin, Madge; Hamdy, Reggie; Reumann, Marie K; Duda, Georg N; Checa, Sara; et al.
ABSTRACT: During bone healing, tissue formation processes are governed by mechanical strain. Sost /sclerostin, a key Wnt signaling inhibitor and mechano‐sensitive pathway, is downregulated in response to mechanical loading. Sclerostin neutralizing antibody (SclAb) increases bone formation. Nevertheless, it remains unclear whether sclerostin inhibition can rescue bone healing in situations of mechanical instability, which otherwise delay healing. We investigated SclAb's influence on tissue formation in a mouse femoral osteotomy, stabilized with rigid or semirigid external fixation. The different fixations allowed different magnitudes of interfragmentary movement during weight bearing, thereby influencing healing outcome. SclAb or vehicle (veh) was administeredand bone healing was assessed at multiple time points up to day 21 postoperatively by in vivo micro‐computed tomography, histomorphometry, biomechanical testing, immunohistochemistry, and gene expression. Our results show that SclAb treatment caused a greater bone volume than veh. However, SclAb could not overcome the characteristic delayed healing of semirigid fixation. Indeed, semirigid fixation resulted in delayed healing with a prolonged endochondral ossification phase characterized by increased cartilage, lower bone volume fraction, and less bony bridging across the osteotomy gap than rigid fixation. In a control setting, SclAb negatively affected later stages of healing under rigid fixation, evidenced by the high degree of endosteal bridging at 21 days in the rigid‐SclAb group compared with rigid‐veh, indicating delayed fracture callus remodeling and bone marrow reconstitution. Under rigid fixation, Sost and sclerostin expression at the gene and protein level, respectively, were increased in SclAb compared with veh‐treated bones, suggesting a negative feedback mechanism. Our results suggest that SclAb could be used to enhance overall bone mass but should be carefully considered in bone healing. SclAb may help to increase bone formation early in the healing process but not during advanced stages of fracture callus remodeling and not to overcome delayed healing in semirigid fixation. © 2018 American Society for Bone and Mineral Research.